2021
DOI: 10.4992/jjpsy.92.20081
|View full text |Cite
|
Sign up to set email alerts
|

外出規制が孤独感・不安・抑うつに及ぼす影響

Abstract: The COVID-19 pandemic in 2020 has threatened people's health and drastically changed their lifestyles. An international collaborative study, Time Social Distancing (TSD), was launched to investigate the effects of the COVID-19 lockdown on time perception and psychological states. The present study obtained longitudinal data from 108 Japanese people in their 20s to 60s over three sessions to investigate how people's loneliness, anxiety, and sleep hygiene changed during confinement, and whether age affected thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Older people, on the other hand, have been shown to be more con dent in the information they received, and have a positive attitude toward what was happening as well as restrictive measures imposed 33 . This was also true in Japan, where the baseline of loneliness, anxiety, and depression increased with age 34 and in general, young, and middle-aged individuals suffered more from the pandemic in terms of mental health than the older adults 21 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Older people, on the other hand, have been shown to be more con dent in the information they received, and have a positive attitude toward what was happening as well as restrictive measures imposed 33 . This was also true in Japan, where the baseline of loneliness, anxiety, and depression increased with age 34 and in general, young, and middle-aged individuals suffered more from the pandemic in terms of mental health than the older adults 21 .…”
Section: Introductionmentioning
confidence: 79%
“…Our results also show that there were differences due to age in the performance of both the spontaneous nger-tapping task and paced nger-tapping task during the pandemic. Age differences were expected since it is well known that adults with older age perform differently in many temporal tasks compared to their younger cohorts 30,[59][60][61][62][63][64] in addition to the fact that the pandemic was lived differently for those with increased age given that multiple studies show young adults suffering more in terms of mental health from the pandemic than their older cohorts 21,[32][33][34][65][66][67] . Though it is well documented that older adults tap at a slower rate than younger adults 58,59 , in this concrete study, we found that in general, adults in the later stage of adulthood were tapping at a faster rate than those in the early stage of adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Older people, on the other hand, have been shown to be more confident in the information they received, and have a positive attitude toward what was happening as well as restrictive measures imposed 33 . This was also true in Japan, where the baseline of loneliness, anxiety, and depression increased with age 34 and in general, young, and middle-aged individuals suffered more from the pandemic in terms of mental health than the older adults 21 .…”
Section: Introductionmentioning
confidence: 79%
“…More concretely, different trends for how the pandemic affected the behavioral performance was observed for different age groups. Age differences were expected since it is well known that adults with older age perform differently in many temporal tasks compared to their younger cohorts 30 , 61 66 in addition to the fact that the pandemic was lived differently for those with increased age given that multiple studies show young adults suffering more in terms of mental health from the pandemic than their older cohorts 21 , 32 34 , 67 69 . Though it is well documented that older adults tap at a slower rate than younger adults 59 , 61 , in this concrete study, we found that in general, adults in the later stage of adulthood were tapping at a faster rate than those in the early stage of adulthood.…”
Section: Discussionmentioning
confidence: 99%